ANALISIS IMPLEMENTASI AKAD SYARIAH DAN ETIKA BISNIS ISLAM PADA KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH (KSPPS) BAYTUL IKHTIAR CABANG CIPANAS KABUPATEN LEBAK TERHADAP LOYALITAS ANGGOTA - Andriyansyah; Thantawi, Tubagus Rifqy; Putra, Bayu Purnama (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
Sharia Savings and Loans and Financing Cooperative (KSPPS) is a sharia financial institution that carries out productive business development and investment activities in improving the quality of economic and business activities for Micro, Small and Medium Enterprises (MSMEs), including channeling financing for economic and business activities, as well as encouraging savings. . As a sharia financial institution, KSPPS of course needs to use Islamic business ethics and sharia contracts in carrying out its daily activities both in the office work environment and when providing services to members. This research takes the example of KSPPS Baytul Ikhtiar which applies sharia contracts and Islamic business ethics. Based on the research results, there is an influence between sharia contract variables and Islamic business ethics on member loyalty.